Ion Exchange Properties of the Canine Carotid Artery - Jones, A. W. (1969)
Properties of the ion exchange mechanisms in the arterial wall were investigated by comparing water and electrolyte contents, and by measuring the steady-state entry of (22)Na, (42)K, and (26)Cl under similar in vitro conditions. Overnight incubation of freshly dissected slices at 2°C resulted in an accumulation of sodium, chloride, and water and a loss of potassium. Subsequent incubation at 37°C in a physiological solution resulted in a reversal of these processes. Loss of water, sodium, and chloride at 37°C could also take place into a potassium-free solution. Under all conditions studied the quantity of fast exchanging electrolyte (half time less than 3 min) exceeded that contained in the inulin and sucrose spaces. The excess could not be attributed to connective tissue adsorption. A kinetic model was applied to the flux data which incorporated two simultaneous processes: bulk diffusion and a reversible reaction. The assumption that the cell membrane behaved as a discrete barrier for the exchange of all cell electrolyte was relaxed in this approach. A theory based upon the physicochemical properties of proteins, ions, and water in biological systems provided a physical basis for the kinetic model, and for interpreting the ion exchange properties of the vascular wall.